UPAYA MENINGKATKAN KINERJA GURU DALAM PEMBELAJARAN DI KELAS MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK DI SMP NEGERI 34 MEDAN - Ersada Br Sembiring (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
Collection techniques, namely, observation, discussion, literature study. The data that has been collected was analyzed using qualitative and quantitative analysis. Based on the results of the research that improving teacher performance in carrying out learning, it can be concluded that researchers from peers can facilitate communication between teachers in carrying out learning in class, Researchers from peers can apply teachers to implementing learning in class.